Laser processing of La61.4Al15.9Ni11.35Cu11.35 based functionally graded material bulk metallic glass - Halim, Qayyum; Nik Mohamed, Nik Abdullah; Rejab, M. R. M.; Kamarulzaman, Mohd Kamal; Hisham, Sakinah; Aizzuddin, A.M. (Springer, Singapore, 2023)
Bulk metallic glass (BMG) based on lanthanum is one of the BMG with exceptional glass-forming ability (GFA). The La61.4Al15.9Ni11.35Cu11.35 bulk metallic glasses were treated to a laser processing test in this experiment. The results showed that the best power, frequency, and speed ranges for laser processing of the La61.4Al15.9Ni11.35Cu11.35 BMG samples are 40 – 50 W, 160 – 240 kHz, and 200 – 400 mm/s, respectively. As a result, the current work was effective in producing the Lanthanum-based functionally graded material (FGM) BMG. The positive findings on the laser's microstructural or morphology, give a solid foundation for future advancement research on the La61.4Al15.9Ni11.35Cu11.35 BMG.